245 Changing Demographics of Head Injury During the COVID-19 Pandemic. (28th February 2022) - Chia, C.W.L.; Merola, J.; Taylor, P.; Hayhurst, C.
Abstract: Introduction: Studies have shown that men are more likely to sustain head injuries (HI) due to a higher likelihood of participation in high-risk behaviours. However, the COVID-19 lockdown caused substantial alterations to the daily routines of the Welsh population. We aimed to describe the demographical changes of HI patients caused by this large-scale restriction of public social activity. Method: A retrospective review of our neurosurgical referral database was performed between 1/1/19 to 31/12/20 to extract patient demographics and referral outcomes (admission/advice only) of adult head injury patients. Referrals during lockdown in Wales (26/3/20 – 1/6/20 and 31/10/20 and 2/12/20) were compared with non-lockdown periods in 2019 and 2020. Results: There was no significant difference in HI referral volume in 2019 (n = 1228) vs 2020 (n = 1179) (OR: 0.71; 95% CI: 0.53 – 0.96, p = 0.02). Women were less likely to be admitted in 2019 (OR: 0.60, 95%CI: 0.39 – 0.91, p = 0.02) and 2020 (OR: 0.52, 95%CI: 0.31–0.88, p = 0.01). We observed evidence of interaction by age and sex in lockdown vs non-lockdown (p = 0.02). Most strikingly, there was higher odds of admission in women aged 40–70 years during lockdown (OR: 10.4, 95%CI: 1.13 – 95.8, p = 0.04). Conclusions: We observed significant demographical shifts in HI during lockdown periods, with striking increases in admission rates of men under 40 years and women aged 40–70. The cause of these substantial changes need clarification and have important public health implications. Given likely reduced road traffic accidents during lockdown, other factors such as alcohol or assault need considering.